Tourism Supply Efficiency: An Analysis of Countries in the Asia-Pacific Region - NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).26, 2021)
The objective of this research is to analyze the factors affecting the tourism supply and its efficiency of the tourism supply for countries in the Asia-Pacific region. The method uses the stochastic frontier with Maximum Likelihood Estimation (MLE) analyzed by Frontier software. 4.1. The data were collected from panel data from 2010 - 2019 for 23 countries. The results of the study revealed that 1) Tourism investment from the private sector and timing factors positively affect the tourism supply of countries in the Asia-Pacific region, while the tourism labor value factor has a negative effect on the tourism supply of countries in the region 2) For the technical performance measurement of tourism supply in each sub-region in the Asia-Pacific region, the average is between 0.387 and 0.657. East Asia shows the highest technical efficiency in China, Hong Kong, Japan, Macau and Mongolia while South Asia has the lowest technical efficiency in Bangladesh, India, Nepal, Pakistan, Sri Lanka and the Maldives, respectively.